Atributos químicos e microbiológicos de solo cultivado com cana-de-açúcar sob manejo convencional e orgânico - Zorel, Daiane (2011)
The identification of soil quality indicators that demonstrate the alterations occurred in areas under organic management is important to determine the sustainability of this kind of cultivation. The soil microbial biomass and activity have been considered as important indicators of soil quality, especially when different management systems are employed in agroecosystems. In this context, the aim of this work was to evaluate management systems (organic and conventional) of the sugar cane over the soil quality, analyzing the chemical attributes as organic matter, pH, potential acidity, aluminium, magnesium, calcium, potassium, cation-exchange capacity, (CEC), sum of bases (SB), and percent base saturation (%BS), as well as the microbiological attributes as number of fungi and bacteria, microbial biomass carbon (MBC), basal respiration (BR) and metabolic quotient (MQ). The soil analyses were taken in the period comprised between May/2009 and September/2010. Among the chemical parameters that most showed the alterations in soil caused by the management are pH, magnesium concentration, potential acidity, SB and %BS. Higher values obtained with these two last parameters in the organic systems with addition of compost and limestone (SOCA) or compost and corrective, especially, indicate soil fertility. There was no significant difference among the treatments concerning MBC probably because it is an area where only recently the experiments were established. An influence of the sampling period was observed, with high values in the higher rainfall period. Higher values of BR were detected in the organic systems, especially in May and August/2009, which was coincident with the higher rainfall period and temperature. Although no significant difference was verified, the higher values of MQ were verified in the conventional system. Concerning the number of fungi and bacteria, the microbial community seemed to respond better to the climate/rhizosphere than the treatments involving the different management systems. Among the parameters studied, the BR was the most effective parameter to detect changes that occur in the soil due to the management system, showing that the organic system altered the soil quality, which reflected in the microbial activity.